L'effectivité des décisions de justice en droit public interne [constitutionnel] - Pigeon, Louis-Philippe (Les Cahiers de droit, 1985)
In practice, no question ever arises respecting the effectiveness of judicial decisions in matters of public law. Whether or not a judgment is technically executory is of no importance. There is such a high degree of respect for the decisions of the courts, specially those of the Supreme Court of Canada, that public authorities practically never feel free to seek a way out of compliance with a judicial pronouncement. Remedial powers of the courts are entrenched under the Canadian Charter of Rights and Freedoms and the Constitution is declared to be the supreme law of Canada. There is thus very limited scope for governmental action in defiance of court orders. The only specific provision for such action appears to be a section of the Extradition Act authorizing the Minister of Justice to refuse to surrender a fugitive if he determines that the latter's offence is of a political character.